OPTIMALISASI PEMANFAATAN DANA DESA UNTUK USAHA TANI DALAM MEWUJUDKAN DESA MANDIRI DI DESA LUENG BARO KECAMATAN SUNGAI MAS KABUPATEN ACEH BARAT - Sara Yulis; Cici Darmayanti; Ikhsan Ikhsan; Cut Sri Firman Hastuti (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2022)
The highest amount of village funds in Lueng Baro Village is in 2021 at Rp. 1,006,174,231,- where the funds are used for other fields such as the village government of Rp. 424,174,226, - the area of gampong development is Rp. 443,220,000, - in the field of community development, amounting to Rp. 39,550,000, - in the field of community empowerment of Rp. 111.900.000,- and the field of disaster management is Rp. 47.330.000,-. The purpose of this study was to determine the efforts made by the local government to optimize village funds in the agricultural sector. This type of research is qualitative using interview guidelines. The number of samples or informants in this study were 8 people. Based on the results of the research that has been carried out, it is obtained that the Efforts made by the Regional Government for Optimizing Village Funds in the Agriculture Sector to realize an independent village is that the village government supports it is to help make proposals for farmer groups and letters needed by farmers to get assistance from other parties such as the local government agency. agriculture for agricultural assistance. Provide village fund assistance for agriculture. Furthermore, the village independence of the farming community is good, although it is not fully independent. However, they no longer depend entirely on government assistance to run their agriculture, they work on their own to meet their agricultural needs and work together to build agricultural roads.